ARUS URBANISASI DAN SMART CITY - Yusriani Sapta Dewi (PROSIDING SNITek, 2017)
Urbanization is a major phenomenon in urban development and is a natural phenomenon in linewith economic development and the level of welfare of the population in a country. Increased urbanpopulation growth will cause various problems and bring consequences in all aspects of urban lifeincluding various positive and negative impacts. . Rapid urban population growth, it is difficult tofollow the capacity of the city's carrying capacity. Cities with population growth will bear morecomplex problems; While natural resources and energy are increasingly limited. So far, the varioussolutions offered are conventional and not quick in responding to more and more problems. In orderfor urban development to be sustainable, solutions need to be done. Smart city is a solution to meetexpectations and minimize the impact of urbanization.